The channels of international comovement - Omar Barbiero (Federal Reserve Bank of Boston, 2023)
How does exposure to international markets affect returns and cash flow comovements? Foreign bond owners, lenders, affiliates, investors, customers, and suppliers all transmit country shocks to companies. Most multinationals have many of these exposures simultaneously within the same foreign market. Returns and cash flows of two companies comove when exposed to the same country through the same channel. Within-country exposure through different channels is generally associated with lower comovement, in line with an operational hedging strategy. This evidence can help reconcile how, on average, increased market integration does not lead to increased comovement.
Keywords: E44; F21; F23; F34; G11; G15; 330; Return comovement; business cycle; multinationals; FDI; international financing; supply chain; foreign exposure